Constructing Beliefs: Media, Identity, and Social Attitudes in the Digital Age - Subiantoro, Anjar (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
This narrative review investigates how various media forms influence social perception and the formation of attitudes, focusing on narrative persuasion, framing effects, identity construction, and cross-cultural implications. The study begins by situating the relevance of the topic within the broader landscape of media influence on individual and collective behavior, especially in the digital age. Using a structured narrative review search across Scopus, PubMed, and Google Scholar, literature was collected based on relevant keywords such as "media influence," "social perception," and "attitude formation," with rigorous inclusion and exclusion criteria guiding selection. The review identifies four key themes. First, narrative persuasion significantly alters attitudes by fostering emotional engagement and reducing counterarguments. Second, media framing influences public interpretation of events and policies, shaping political and social opinions. Third, social media platforms contribute to identity construction and the reinforcement of social norms, particularly among youth and marginalized communities. Fourth, cross-cultural comparisons show that media effects vary by region, mediated by cultural values, political systems, and media literacy levels. The review concludes that media is a powerful agent in shaping public opinion, necessitating policy interventions that promote algorithmic transparency and educational programs in media literacy. Understanding the complex dynamics of media influence is essential for cultivating informed societies capable of navigating an increasingly mediated world.